Spatial and Temporal Distribution of Benthic Dinoflagellates on Artificial Substrate at Seribu Islands Waters - Widiarti, Riani; Ilyas, Ahmad Jutrzenka; Triputra, Kresnanda; Kusuma, Muhammad Praja; Rachman, Arief; Hii, Tan Toh (Marine Science Department Diponegoro University, 2024)
Damage to coral reef ecosystems and changes in water quality are capable of increasing the abundance of benthic dinoflagellates which could cause Ciguatera Fish Poisoning (CFP). Therefore, this research aimed to observe spatial and temporal abundance of those potential benthic dinoflagellates and analyze their relationship with environmental factors. Sampling was carried out on September 21-24, 2023 in Pramuka Island, Seribu Islands district, with different treatments, namely depth, location and time. Research conducted by deploy several series of artificial substrates into the waters, and the benthic dinoflagellates were collected from the artificial substrate placed in 1, 3, and 5 meter of water depths for 24, 48, and 72 hours at Odi, Mazu, and Villa Delima Piers. Cell densities were determined by enumeration using a Sedgewick Rafter Counting Chamber under a light microscope, and the relationship with environmental parameters was analyzed by using Principal Component Analysis (PCA). The results showed that 4 genera of benthic dinoflagellates which had the potential to cause CFP, were attached to the artificial substrate, namely Amphidinium, Coolia, Ostreopsis, and Prorocentrum. Prorocentrum cells were observed in highest number on artificial substrates at every treatment with different depths, locations, and times. Furthermore, the PCA analysis showed the abundance of Prorocentrum was influenced by the most typical environmental parameters at each depth, location, and time, namely temperature, nitrate, DO, and light intensity. The research provided valuable information on the benthic dinoflagellates both spatially and temporally, through international standard methods in order to prevent and anticipate negative impacts caused by CFP.